Why Hospitals Can, and Should, Do More to Help With Public Health. Issue 5 (September 2016) - Sibbald, Shannon; Graham, Ross
Abstract : This editorial presents the rationale for hospitals to take on a larger advocacy role and hospital advocacy to be reinstated as a requirement for health system transformation.